Bartering as a Blind Spot: A Call to Action from COVID‐19. Issue 4 (29th September 2020) - Gunia, Brian C.; Lewicki, Roy J.
Abstract : Bartering is a common form of negotiation, and COVID‐19 may have heightened its occurrence at least temporarily. Yet, bartering has received little attention in the negotiation literature. After defining bartering and describing its relevance and prevalence in the COVID‐19 era, this article suggests that an understanding of bartering would significantly enhance our understanding of negotiation in general. Two broad research questions illustrate the importance of better understanding bartering, with important theoretical, pedagogical, and practical implications.